Assessment of Aerodynamic Performance of Darrieus H-Rotor Wind Turbine Using Realizable k–ε Turbulence Model Approach - Ariefianto, Rizki Mendung; Fridayana, Elyas Nur; Wardhana, Wisnu (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
Wind energy extraction gains more attractiveness as the development of renewable energy progresses and the reduction of fossil fuel usage becomes imperative. Consequently, numerous efforts have been made to enhance turbine performance, such as with the Darrieus H-Rotor type, through numerical studies. Computational Fluid Dynamics (CFD) has become a prevalent tool for these studies, utilizing various approaches, including the eddy viscosity model based on the Boussinesq hypothesis, which underpins turbulence models. This research evaluates the performance of the Darrieus H-Rotor Wind Turbine via 2D CFD modeling using the Realizable k–ε turbulence model. The study also considers simulations with the Double Multiple Streamtube (DMST) model and other turbulence models applied to similar turbine geometries, with experimental data serving as validation benchmarks. Approximately 140,000 cells were utilized in the meshing process to balance simulation duration and the accuracy of the Cp value. The results indicate that the Realizable k–ε turbulence model performs satisfactorily, particularly in producing accurate Cp values in the pre-stall region. The comparison of average Cp values against experimental data across eight tip speed ratio points further supports the effectiveness of the Realizable k–ε turbulence model in simulating the aerodynamic performance of the Darrieus H-Rotor Wind Turbine. Nonetheless, the Realizable k–ε turbulence model fails to enable the Darrieus H-Rotor Wind Turbine to achieve positive Cm values across the entire azimuthal angle at lower tip speed ratios, thus not reaching effective self-starting conditions.